Cognition, emotional health, and immunological markers in children with long-term nonprogressive HIV - Robert Paul (2018)
© 2018 Wolters Kluwer Health, Inc. Background: HIV-infected children with long-term nonprogressive (LTNP) disease eventually convert to a progressive disease type, yet the extent to which these children experience the cognitive and emotional symptoms observed in typical progressive HIV (Progressors) is unknown. Methods: Eighty-eight LTNPs, 53 Progressors, and 323 healthy controls completed annual assessments of cognitive and emotional health as part of a prospective study. The 2 HIV-infected groups and the healthy controls were matched on age and sex distribution at enrollment. Plasma HIV RNA, T-cell counts/percentages, activated monocytes, perivascular monocytes, and markers of macrophage activation (sCD163 and sCD14) were compared by progression subtype. Cognitive and emotional outcomes were compared using cross-sectional linear regression analysis and longitudinal sensitivity models. Results: LTNPs exhibited the same cognitive phenotype and emotional dysregulation as Progressors, with worse outcomes in both groups compared with controls. In addition, cognitive and emotional symptoms were evident before children reached the minimum age for LTNP designation (8 years). Baseline plasma HIV RNA, sCD163, activated monocytes, and perivascular monocytes were lower in LTNPs versus Progressors, with no difference in T-cell counts/percentages or sCD14 levels. Most LTNPs converted to a progressive disease subtype during the study, with similar cognitive and emotion profiles between these subgroups. Conclusions: Pediatric LTNPs experience cognitive and emotional difficulties that mirror symptoms of progressive disease. The abnormalities are present at young ages and persist independent of plasma T-cell counts. The findings highlight the neurodevelopmental risk of pediatric HIV, even in those with early innate disease control.